Decreased enzyme activities, ammonification rate and ammonifiers contribute to higher nitrogen retention in hyperthermophilic pretreatment composting. (January 2019) - Huang, Ying; Li, Danyang; Wang, Lin; Yong, Cheng; Sun, Enhui; Jin, Hongmei; Huang, Hongying
Highlights: Hyperthermophilic pretreatment composting (HPC) resulted to higher N retention. Bacterial and fungal ammonifiers decreased remarkably in HPC. Declined ammonification and enzymes activity contribute to higher N retention in HPC. Abstract: Hyperthermophilic pretreatment composting (HPC) is superior to traditional composting (TC) with shortened maturity period and increased nitrogen (N) retention. However, the mechanism associated with N retention in HPC remains unclear. In this study, we compared the impact of HPC and TC on N retention, and found the proportion of N retained in the final compost was 83.3% and 67.2% for HPC and TC, respectively. Decreased ammonification rate, urease and protease activities together with an elevated temperature were found in HPC. Illumina amplicon sequencing showed that HPC caused a major decline in microbial community richness and diversity in the thermophilic phase. Notably, bacterial ( Pseudomonas and Bacillus ) and fungal ammonifiers ( Acremonium, Alternaria and Penicillium ) decreased remarkably in HPC during this phase. Changes in the microbial community could be related to unfavorable modifications of environment from HPC, and which resulted in decreased ammonification and enzyme activities and improved N retention.